TINGKAT KEBERHASILAN PENETASAN PENYU LEKANG (Lepidochelys olivacea) PADA SARANG SEMI ALAMI (Jurnal Bioconcetta, 2022)
This study aims to determine the success rate of hatching olive ridley turtle eggs (Lepidochelys olivacea) in semi-natural nests. This study used a descriptive method by direct observation of turtle eggs from conservation activists. The research was carried out in two locations, namely at the Jambak Sea Turtle Camp location, 3 nests of olive ridley turtle eggs (79 turtle eggs in the first nest, 81 turtle eggs in the second nest and 96 eggs in the third nest). The second location is at UPT Pariaman Turtle Conservation with 2 nests (first nest 100 turtle eggs, second nest 80 turtle eggs). The results showed that the hatching percentage of olive ridley turtle eggs in semi-natural nests at UPT Pariaman Turtle Conservation was 63.89%, at Jambak Sea Turtle Camp 40.63%. It can be concluded that allocating turtle eggs to semi-natural nests increases the hatching success of olive ridley turtle eggs (Lepidochelys olivacea).